ANALISIS PENCATATAN PEMBAYARAN PAJAK PENGHASILAN PADA UMKM DI WILAYAH SEMARANG (Students' Journal of Accounting and Banking, 2013)
This study aims to determine the condition of payment of taxes MSMEs in Semarang Region, ow to record income tax payments made by SMEs in the area of Semarang,and whether SMEs keep records in case of an underpayment or overpayment. The population in this study are all taxpayers MSMEs located in Semarang area, while the sample used is representative of most of the studied population or by the number of 86 respondents. Data obtained through primary data by distributing questionnaires to respond and secondary data through some data obtained from the office of Department of Cooperatives and SMEs Semarang. The sampling technique used was convenience sampling. Data analysis was performed using analysis of qualitative deskretif. From the results of these studies in the graph shows that the condition that tax payments made by the majority of respondents obtained information from pertugas tax, The taxpayer has to pay taxes on time, axpayers are aware of the tax rate and the calculation. Results show that the knowledge of the taxpayer, understanding of the tax laws and benefits are met to contribute to the tax reporting, dan UMKM pernah mengalami lebih bayar atau kurang bayar dalam pembayaran pajaknya, SMEs also make adjustments in the event of overpayment or underpayment although adjustment is done not in accordance with Financial Accounting Standards Small and Medium Enterprises. Keywords: MSME ,Listing,Payment,Adaptation Income Tax,